LEVEL OF PROCALCITONIN PLASMA AS AN EARLY SEPSIS BIOMARKER IN POLYTRAUMA PATIENTS IN DR HASAN SADIKIN GENERAL HOSPITAL BANDUNG - Ricky Wibowo; Hermawan Nagar Rasyid; Darmadji Ismono (Universitas Airlangga, 2019)
Background: Polytrauma patients have a risk of progressive organ dysfunction due to uncontrolled immunological process. Sepsis and multiple organ failure are the most common causes of morbidity and mortality in late death of polytrauma patients. Clinical diagnosis and routine laboratory test are not specific until the patient entered a critical state. Delayed diagnosis of sepsis is caused by difficulties in diagnosing. Procalcitonin is a biomarker that is useful in predicting the onset of sepsis. The aim of this research is to determine the level of procalcitonin as early biomarker sepsis in polytrauma patients in RSHS Bandung. Methods: A diagnostic study using secondary data from the Academic Leadership Grant (ALG) study on polytrauma patients in Emergency Room of RSHS Bandung from January-June 2017. This study determined the cut of point, sensitivity, spesificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV), and accuracy to diagnosis sepsis.Result: A total of 70 subjects were enrolled in this study, 92.9% were male gender with average age 33.21±13.395 years old. Twenty-one patients (30%) were diagnosed with sepsis. Based on receiver operating characteristic (ROC) curve showed the level of procalcitonin was given in the area under curve (AUC) 0.96 with Confidence Interval 0.923-1.00 (p < 0.05). The Procalcitonin cut of point was 1.46 ng/mL with a sensitivity of 90.5%, specificity of 89.8%, PPV of 79.2%, NPV of 95.7%, and accuracy of 90.0%.Conclusion: Plasma Procalcitonin 1.46 ng/mL is a good predictor for early diagnosis sepsis toward polytrauma patients.